Present status and future prospective of hydroponics technique: hope and hype for future welfare - Jagtap, P P; Bhakar, S R; Lakhawat , S S; Singh, P K; Kothari, M (Journal of Postharvest Technology, 2022)
Soil based cultivation is now facing difficulties due to different man made reasons such as deforestation, industrialization and urbanization.  Besides, sudden natural disasters, climate change and unlimited utilization of chemicals for agriculture purposes cause the depletion of land  fertility and quality. With the advent of civilization, open field/soil-based agriculture is facing some major challenges; most importantly decrease  in per capita land availability. Under such circumstances, in near future it will become impossible to feed the entire population using open field  system of agricultural production only. That is why, scientists have developed a new alternative approach for cultivation system namely soil less cultivation or hydroponics. Hydroponics is a soil-less culture technique in which plant can grow in a liquid or water solution. Hydroponic is  a method of growing plants using mineral solution, in water, without soil. This method can be extremely helpful to countries that have poor  land, which is not able to sustain agriculture. A large number of plants and crops or vegetables can grow by hydroponics culture The quality of  yield, taste and nutritive value of end products is generally higher than the natural soil based cultivation. This cultivation is cost efficient,  disease free and eco-friendly as well as getting popularity all over the world, both the developed and the developing countries.
Keywords: Soil-less culture; , hydroponics; nutrient solution; growth medium; , cost efficient